Selection and Scaling Time History Records for Performance-Based Design - Fahjan, Yasin M.; Kara, F. Ilknur; Mert, Aydin (Igi Global, 2017)
Recent developments in performance-based analyses and the high performance of computational facilities have led to an increased trend for utilizing nonlinear time-history analysis in seismic evaluation of the performance of structures. One of the crucial issues of such analysis is the selection of appropriate acceleration time histories set that satisfy design code requirements at a specific site. In literature, there are three sources of acceleration time histories: 1) recorded accelerograms in real earthquakes scaled to match design code spectrum/uniform hazard spectra/conditional mean spectrum, 2) artificial records generated from white noise spectra to satisfy design code spectrum, and 3) synthetic records obtained from seismological models. Due to the increase of available strong ground motion database, using and scaling real recorded accelerograms is becoming one of the most contemporary research issues in this field. In this study, basic methodologies and criteria for selecting strong ground motion time histories are discussed. Design code requirements for scaling are summarized for ASCE/SEI-7-10, EC8 and Turkish Seismic Codes. Examples for scaling earthquake records to uniform hazard spectra are provided.
Keywords: Earthquake Ground-Motion; Simulation; Spectrum; Fault; Accelerograms; Aftershocks; Generation; Frequency; Duration; Models